2013
DOI: 10.1128/aem.03034-12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Putatively Thermophilic Anaerobic Methanotrophs in Diffuse Hydrothermal Vent Fluids

Abstract: The anaerobic oxidation of methane (AOM) is carried out by a globally distributed group of uncultivated Euryarchaeota, the anaerobic methanotrophic arachaea (ANME). In this work, we used G؉C analysis of 16S rRNA genes to identify a putatively thermophilic ANME group and applied newly designed primers to study its distribution in low-temperature diffuse vent fluids from deep-sea hydrothermal vents. We found that the G؉C content of the 16S rRNA genes (P GC ) is significantly higher in the ANME-1GBa group than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
0
31
0
1
Order By: Relevance
“…In addition, possible microbial components of thermophilic anaerobic methane oxidizers, consortia of ANME-1a Archaea and HotSeep-1 cluster Deltaproteobacteria, have been identified via FISH analysis (Holler et al 2011). Similar phylotypes of potentially thermophilic ANME-1a Archaea have also been found in hydrothermal sediments and diffusing fluids of SED hydrothermal systems such as the Axial Seamount and Endeavour Segment fields in the Juan de Fuca Ridge and the Yonaguni Knoll IV field in the Okinawa Trough (Nunoura et al 2010;Merkel et al 2013). Because these phylotypes of thermophilic anaerobic methanotrophic Archaea remain resistant to cultivation, quantitative cultivation methods are not feasible.…”
Section: Chimney Structures and Sedimentsmentioning
confidence: 93%
“…In addition, possible microbial components of thermophilic anaerobic methane oxidizers, consortia of ANME-1a Archaea and HotSeep-1 cluster Deltaproteobacteria, have been identified via FISH analysis (Holler et al 2011). Similar phylotypes of potentially thermophilic ANME-1a Archaea have also been found in hydrothermal sediments and diffusing fluids of SED hydrothermal systems such as the Axial Seamount and Endeavour Segment fields in the Juan de Fuca Ridge and the Yonaguni Knoll IV field in the Okinawa Trough (Nunoura et al 2010;Merkel et al 2013). Because these phylotypes of thermophilic anaerobic methanotrophic Archaea remain resistant to cultivation, quantitative cultivation methods are not feasible.…”
Section: Chimney Structures and Sedimentsmentioning
confidence: 93%
“…60 to >90°C), and concomitant δ 13 C-CH 4 and DIC signatures of biogenic methane oxidation (Biddle et al, 2012). These high-temperature ANMEs are not limited to Guaymas Basin, but are widespread in methane-rich hydrothermal fluids at different vent sites (Merkel et al, 2012). Laboratory incubations and enrichments of sulfate-dependent, anaerobic methane oxidizing microbial populations from Guaymas Basin indicated a temperature limit of ca.…”
Section: High-temperature Methane and Sulfur Cyclingmentioning
confidence: 99%
“…Molecular ecological studies have indicated that the ANME-1 populations occur in deeper, more reductive and more sulfate-depleted habitats than the ANME-2 populations (Knittel et al, 2005;Krüger et al, 2008;Nunoura et al, 2008;Rossel et al, 2011;Yanagawa et al, 2011). Furthermore, the potentially thermophilic ANME-1 group has been recognized as a key component in certain hydrothermal ecosystems, such as Guaymas Basin and Juan de Fuca Ridge (Biddle et al, 2012;Lever et al, 2013;Merkel et al, 2013). This mcrA group of thermophilic ANME-1 is defined as Hydrothermal ANME-1 Cluster II (Lever et al, 2013) (alternatively classified as mcrA-Guaymas (Biddle et al, 2012) or ANME-1GBa (Merkel et al, 2013)).…”
Section: Microbial Functions Of Methanogenesis and Aommentioning
confidence: 99%
“…Furthermore, the potentially thermophilic ANME-1 group has been recognized as a key component in certain hydrothermal ecosystems, such as Guaymas Basin and Juan de Fuca Ridge (Biddle et al, 2012;Lever et al, 2013;Merkel et al, 2013). This mcrA group of thermophilic ANME-1 is defined as Hydrothermal ANME-1 Cluster II (Lever et al, 2013) (alternatively classified as mcrA-Guaymas (Biddle et al, 2012) or ANME-1GBa (Merkel et al, 2013)). The optimal growth temperatures of the thermophilic ANME-1 in the Guaymas site have been estimated to be above 70°C (Merkel et al, 2013).…”
Section: Microbial Functions Of Methanogenesis and Aommentioning
confidence: 99%
See 1 more Smart Citation